2020
DOI: 10.1029/2019je006086
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Gravity Field Models from GRAIL Data and Implications for Models of the Density Structure of the Moon's Crust

Abstract: We present our latest high‐resolution lunar gravity field model of degree and order 1200 in spherical harmonics using Gravity Recovery and Interior Laboratory (GRAIL) data. In addition to a model with the standard spectral Kaula regularization constraint, we determine models by applying a constraint based on topography called rank‐minus‐one (RM1). The new models using this RM1 constraint have high correlations with topography over the entire degree range by design. The RM1 models allow the determination of app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 68 publications
0
78
0
Order By: Relevance
“…The GRAIL nominal and extended mission data (Goossens et al, 2018) analyzed and discussed here permit higher resolution gravity modeling than in previous studies (e.g., Kiefer et al, 2013;Evans et al, 2016). These data demonstrate that the amplitude of the four PBGAs cannot be explained by mare-filled craters alone, as inferred by Evans et al (2016), and instead require an additional density contrast.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…The GRAIL nominal and extended mission data (Goossens et al, 2018) analyzed and discussed here permit higher resolution gravity modeling than in previous studies (e.g., Kiefer et al, 2013;Evans et al, 2016). These data demonstrate that the amplitude of the four PBGAs cannot be explained by mare-filled craters alone, as inferred by Evans et al (2016), and instead require an additional density contrast.…”
Section: Discussionmentioning
confidence: 58%
“…Four positive Bouguer gravity anomalies in Oceanus Procellarum. GRAIL-derived Bouguer spherical harmonic solution to degree 6-660 is displayed on the left, with an assumed density correction of 2800 kg/m 3 , windowed from a global, locally patched, constrained solution (GRGM1200B_RM1_1E1; Goossens et al, 2018). Surface elevations, measured from the LOLA 1060 instrument (Smith et al, 2010), are shown on the right.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations